Shooting Errors Simulations Initiated by Barrel Jumping of 40 mm Turret Guns - Aleksandar KARI; Olivera JEREMIĆ; Momčilo MILINOVIĆ; Damir JERKOVIĆ; Miloš MARKOVIĆ (Problemy Mechatroniki)
Model considered estimations of isolated shooting errors initiated by barrel jumping after each particular bullet as the research of particular characteristic important for gun mounting on the mobile platforms. Sequential influences of barrel disturbances are included in the initial ballistics derivations independent of vehicle turret and undercarriage. Expected disturbance magnitudes are analyzed during and beyond shooting for the particular bullet in the ripple. Shooting ripple errors are analyzed according to the angular disturbances transposed to the projectile initial ballistic elements. Rate of barrel impeachments during firing is taken as the element of projectile spin disturbance. Barrel system with appropriate recoil equipment is taken as the rigid body model in the first approximation. Behaviour of 40 mm automatic gun as the possible concept aimed at the shooting with small elevation angles, as mounted on the mobile combat platforms was tested. Ballistic testing of real projectiles on the proving ground is used as reference to selected gun particular errors. Further extended research was directed to the system’s acceptable accuracy and stability in the cases of gun mounting on the Armour Personal Carrier (APC).